2017
DOI: 10.1289/ehp1674
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and Dose-Specific Effects of Maternal Bisphenol A Exposure on Pancreatic Islets of First- and Second-Generation Adult Mice Offspring

Abstract: Background:Exposure to the environmental endocrine disruptor bisphenol A (BPA) is ubiquitous and associated with the increased risk of diabetes and obesity. However, the underlying mechanisms remain unknown. We recently demonstrated that perinatal BPA exposure is associated with higher body fat, impaired glucose tolerance, and reduced insulin secretion in first- (F1) and second-generation (F2) C57BL/6J male mice offspring.Objective:We sought to determine the multigenerational effects of maternal bisphenol A ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 119 publications
(147 reference statements)
6
90
0
Order By: Relevance
“…BPA is used as a coating for the inside of food cans, water bottles, baby bottles and some dental fillings (Calafat, Ye, Wong, Reidy, & Needham, ; Takahashi & Oishi, ). It has been reported that BPA is leached from food and beverage containers, and some dental sealants and composites (Howe & Borodinsky, ; Yamamoto & Yasuhara, ) which has been linked with onset of various health disorders such as diabetes, obesity, cardiovascular diseases or carcinogenesis (Adoamnei et al, ; Bansal et al, ; Fénichel & Chevalier, ; Lombó et al, ; Manfo, Jubendradass, Nantia, Moundipa, & Mathur,; Rubin, ). BPA has also been involved in impairing fertility in both men and women as evident by recurrent miscarriages or premature births in women (Rubin, ) or decrease in semen quality and DNA damage of spermatozoa in men (Li et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…BPA is used as a coating for the inside of food cans, water bottles, baby bottles and some dental fillings (Calafat, Ye, Wong, Reidy, & Needham, ; Takahashi & Oishi, ). It has been reported that BPA is leached from food and beverage containers, and some dental sealants and composites (Howe & Borodinsky, ; Yamamoto & Yasuhara, ) which has been linked with onset of various health disorders such as diabetes, obesity, cardiovascular diseases or carcinogenesis (Adoamnei et al, ; Bansal et al, ; Fénichel & Chevalier, ; Lombó et al, ; Manfo, Jubendradass, Nantia, Moundipa, & Mathur,; Rubin, ). BPA has also been involved in impairing fertility in both men and women as evident by recurrent miscarriages or premature births in women (Rubin, ) or decrease in semen quality and DNA damage of spermatozoa in men (Li et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…BPA exposure can also lead to disruptions in DNA methylation and histone acetylation patterns [144]. Also, as was shown with atrazine exposure, a potential epigenetic transgenerational effect (on insulin production in this case) has been reported in F1 and F2 mouse offspring after maternal BPA exposure [145]. Additionally, this effect may be linked with changes in germ line cells affecting the animal's fertility (see Chianese et al, 2017 for review [146]).…”
Section: Discussionmentioning
confidence: 80%
“…Conclusions also suggest that ketogenic-diet is better only through the overall calorie consumption is matched [22]. In one research [18], people on keto lose 2.2 times further fat than that on small-calorie, small-fat diets. The amounts of triglyceride, as well as HDL lipids, have also increased.…”
Section: The Mechanism Of Ketogenic-diet In Reducing the Weight Of Oumentioning
confidence: 91%
“…Recent research [18] provides strong evidence of a greater weight loss in people on a ketogenic or extremely low caloric intake relative to those on a somewhat more conventional reduced-fat diet or Caribbean diet. Nevertheless, the disparity in losing weight tends to vanish over the period.…”
Section: Effect Of a Ketogenic Diet On Our Bodymentioning
confidence: 99%
See 1 more Smart Citation